Managing risks in commercial and retail banking - Ghosh, Amalendu (Hoboken, N. J. : John Wiley & Sons, 2012)
'Managing Risks in Commercial and Retail Banking takes an in-depth, logical look at dealing with all aspects of risk management within the banking sector. It presents complex processes in a simplified way by providing real-life situations and examples. The book examines all dimensions of the risks that banks face--both the financial risks--credit, market, and operational--and the non-financial risks--money laundering, information technology, business strategy, legal, and reputational. Focusing on methods and models for identifying, measuring, monitoring, and controlling risks, it provides practical advice backed up by solid theories, without resorting to the use of complicated mathematical and statistical formulas. Author Amalendu Ghosh exposes topics that are usually absent in books on managing banking risk--such as design of control framework, risk management architecture, credit risk rating, risk-based loan pricing, portfolio analysis, business continuity planning, and corporate governance. [The] Author has extensive experience with a variety of major banks and institutions worldwide and brings a fresh perspective in the wake of the global finance crisis. [He] Presents a novel approach using models of the credit risk rating of different types of borrowers, the methodology for assigning weights for deriving the rating, and the scoring process. [This book] Covers the essentials of corporate governance and options for credit risk assessment in line with the recommendations made in the New Basel Capital Accord. [It also] Explains the methodology of risk-based internal audit, including techniques to enable bank branches to switch over from the old transaction-based audit methods. With its logical sequence of the aspects of risk management, the book's layout is ideal for presentations, making it a handy tool for risk management training
Includes bibliographical references and index.
Keywords: Banks and banking -- Risk management; Risk management; Financial risk management; Banks and banking